OPTIMIZATION OF THE DEVELOPMENT OF A PLASTIC RECYCLING MACHINE (Nigerian Journal of Technology, 2009)
This research involves the design and construction of a plastic recycling machine that minimizes the limitations of the already existing (imported) ones to a great extent and at the same time ensuring effective waste management. The results of experimental analysis show that for every used plastic fed into the hopper, about temperature of 200oC is required to melt it. The machine employs the principle of conveying and heating to effect shredding and melting of the materials fed through the hopper, and requires only two persons to operate. The machine is designed using locally available raw materials which make it cheap and easy to maintain and repair. The performance test analysis carried out defines the characteristics of the machine and shows that at a speed of 268 rpm the machine functions effectively and efficiently in performing its task producing a high finishing recycling efficiency or recyclability of 97%, takes 2 minutes to recycle a batch of plastics and has a recycling capacity/throughput of about 265 Kg/hr which translates to a significant time. It is cost and energy saving since its specific mechanical energy consumption is low at about 30.23KJ/Kg. Experiments also show that for a batch process, power requirement of the machine is proportional to the time in process.